DIRECTIONS OF PROVIDING EMPLOYMENT OF THE POPULATION (IN THE EXAMPLE OF THE REPUBLIC OF UZBEKISTAN) - Doniyorova Fotimabonu Alisher kizi (Labor economics and human capital, 2023)
In this article, the directions of ensuring the employment of the population, the factors of unemployment are explained in detail. The level of employment and unemployment of the population in the Republic of Uzbekistan, the dynamics of their change, and the employment of the population were analyzed by sector. Proposals were also developed to ensure the employment of the population and reduce the level of unemployment.